Cost Perspective in the Selection of Cattle Sales Channels (Case Study: Cattle Farmers in Bongomeme) - Reza Putra Moohulalo; Zulkifli Bokiu; Nurharyati Panigoro (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the cost perspective in the selection of cattle sales channels by farmers in Bongomeme, Gorontalo. This study uses a qualitative descriptive approach with primary data obtained through in-depth interviews and observations of four key informants, consisting of farmers who use brokers (dahangi) and those who sell directly. The data were analyzed using the Miles and Huberman interactive model. The results show that farmers experience an illusory profit because they only apply a cash-basis perspective, ignoring opportunity costs such as unpaid personal labor and natural feed. The decision to choose a sales channel is heavily influenced by risk aversion, liquidity needs, and information asymmetry. Farmers who use brokers prioritize risk transfer and fast cash to avoid the fear of price manipulation, while those selling directly optimize margins by utilizing personal assets and digital literacy (social media). The study concludes that direct selling is the most efficient channel when farmers apply a full costing method to accurately calculate the real cost of production.